PENGARUH ATRIBUT PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK PADA PLATFORM E-COMMERCE SHOPEE - Az-zuhaira, Az-zuhaira; Mathori, Muhammad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This research aims to determine the influence of product attributes and service quality on purchasing decisions for cosmetic products on the Shopee e-commerce platform, with a sample of 130 user respondents. This research uses a quantitative method with an online questionnaire via Google Form, which is then processed using descriptive analysis methods, classical assumption testing, and hypothesis testing using SPSS Version 25. The test results show that the product attribute variable (X1) has a positive and significant effect on purchasing decisions, the service quality variable (X2) has a positive and significant effect on purchasing decisions, these two variables simultaneously also influence purchasing decisions, so it can be said that all existing hypotheses in this study it was accepted, namely that it had a positive and significant effect.